THE ROLE OF CONTEXTUAL-BASED DIGITAL ARABIC LANGUAGE LEARNING BOOKS IN HIGHER EDUCATION - Zainur Rohmah Sa'adi; Thohir, Muhammad (University of Islam Malang, 2024)
In general, Arabic language learning in Indonesia, particularly in higher education, faces various challenges such as the scarcity of well-prepared Arabic language learning books and the lack of adequate learning media and resources. Efforts have been made to address these challenges through the introduction of contextual-based digital learning materials. The aim of this research is to explore the role of contextual-based digital learning materials in higher education and to examine students' responses to the availability of contextual-based digital Arabic language learning books. The research methodology employed in this study is qualitative descriptive. Data collection techniques include interviews, observations, and questionnaires. Data analysis follows four stages: data collection, data reduction, data presentation, and drawing conclusions. The findings of the research indicate that the use of contextual-based digital learning materials, presented in the form of modules accessible via computers or Android devices, can capture students' interest and contribute to the improvement of Arabic language learning. Students respond positively to the availability of contextual-based digital Arabic language learning books, as it allows them to explore language knowledge within real-life contexts.